Integrasi Botol Kaca Hancur Sebagai Agregat Dalam Pembuatan Paving Blok Ramah Lingkungan - Masduqi, Iqbal Prihandana; Pratama, Ihza Adha Yaza Putra; Maulana, Muhammad Adrian (Jurnal Teknologi Cerdas, 2024)
This paper titled "Integration of Crushed Glass Bottles as Aggregate in the Production of Environmentally Friendly Paving Blocks" explores the fusion of aesthetic value and sustainability through the use of crushed glass bottles in paving block production. Capitalizing on glass waste, this paper proposes an innovative and ecological approach to the building materials industry. With a focus on reducing waste and promoting a circular economy, the detailed study reveals the capability of glass aggregates to produce products that are not only strong and durable but also aesthetically appealing. The paving blocks made with glass aggregate support the expected structural strength while also exhibiting unique surface beauty, creating the potential for widespread use in sustainable and eco-friendly construction projects. This paper takes a holistic view, emphasizing the social, economic, and environmental implications of using recycled glass, while offering fresh perspectives in the development of greener construction materials